The Implementation of Safety and Reliability of Data Transmission in Railway Signallization Systems - Radomir Brkic; Zivoslav Adamovic (Communications - Scientific letters of the University of Zilina, 2008)
The focus of this paper is the safety and reliability of data transmission in railway systems at increased and high train speeds by means of technological devices of new generation. Routes in railway traffic are protected with new microprocessing signalling devices, the reliability and availability of which, thanks to new techology, may be projected to a necessary, i. e. desired value.